Women Characters In the Novel of Shashi Deshpande, Anita Desai and Rama Mehta: a Psychological Study: Exploring the Role of Women Characters in the Novels of Shashi Deshpande, Anita Desai and Rama Mehta (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The purpose of this paper is to examine the emergence ofthe feminine sensibility as a concept of reality in the fictional world ofAnita Desai, Shashi Deshpande and Rama Mehta. She is one of the most recognizedfigures in Indo- Anglian fiction. The present work attempts to analyse thepsychological study in the novels of Anita Desai, Shashi Deshpande and RamaMehta. I have chosen Anita Desai, Shashi Deshpande and Rama Mehta for myresearch work because she has laid emphasis not only women character's but onmen also.  To conclude I cansay that the feeling of sensitivity, thought, intelligence has attracted mostextensive critical attention in India and abroad. She uses her powersensibilities to observe a life and combines the same with her artistic visionto create memorable characters.